An Empirical Research of Critical Incident of Earthquake Disaster Basedon Credible Association Data Mining - Suyudi, Mochamad; Sukono, Sukono (International Journal of Global Operations Research, 2021)
Earthquake disasters usually cause panic in the community affected areas, so it is necessary to be analyzed to deal with earthquake events in the future. This paper analyzes data from 9 major earthquakes in Indonesia over the past 4 years and determines 14 critical events. The analysis is based on credible association rules (CAR), data mining, and the maximum clique algorithm. To verify the accuracy of the association relationship and CAR effectiveness, it is performed using a maximum clique algorithm. Based on the results of data mining, that earthquakes have a credible association relationship and have a probability of critical events in various regions in Indonesia. Thus, these results can be used for prediction, early warning, and logistic distribution planning.